Fragilização por hidrogênio da liga Ti-6Al-4V ELI: métodos de hidrogenação e caracterização mecânica - Borrut, Loïc Serrigny (Universidade Federal de São Carlos, 2024)
Titanium alloys are highly valued materials due to the combination of various commercially relevant properties, including high specific strength and corrosion resistance, a high melting point, and ductility. The versatility of properties exhibited by these alloys, especially Ti-6Al-4V alloys, makes them attractive for a range of applications, even sparking interest for potential use in offshore oil exploration structures. However, titanium alloys are susceptible to hydrogen embrittlement when exposed to environments containing high concentrations of hydrogen. Structural materials in maritime environments are typically subjected to cathodic protection by impressed current to prevent corrosion. A potential side effect of cathodic protection is the release of hydrogen at the interface between the protected metal and the electrolyte in contact with it, due to hydrogen evolution reactions, which can lead the protected metal to absorb significant amounts of hydrogen. This is a possible limiting factor for the use of titanium alloys in maritime structures. This study aimed to investigate the influence of hydrogen presence on the static mechanical properties of Ti-6Al-4V ELI alloy, especially ductility, to evaluate the susceptibility of this alloy to hydrogen embrittlement. For this purpose, specimens of the study material were subjected to hydrogenation processes for different periods, and subsequently, their mechanical properties were determined through a low-strain rate tensile test. The results of the tensile tests, however, were similar for the non-hydrogenated material and the specimens hydrogenated for different periods, indicating that the hydrogenated specimens did not absorb sufficient amounts of hydrogen to cause embrittlement under the hydrogenation conditions applied in this study.
Hydrogen embrittlement of the Ti-6Al-4V ELI alloy: hydrogenation methods and mechanical characterization
Keywords: Ti-6al-4V; Hidreto; Hidrogênio; Fragilização; Ductilidade; Hydride; Hydrogen; Embrittlement; Ductility; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA